Early nasal reconstruction after skin-preserving excision of squamous cell carcinoma of the nasal vestibule - Federspil, Philippe A.; Plinkert, Peter K.; Plath, Karim (Journal of plastic, reconstructive & aesthetic surgery, 2020)
Surgery for early-stage squamous cell carcinoma of the nasal vestibule (SCCNV) may lead to facial disfigurement. We wanted to investigate if skin-preserving excision of SCCNV with reconstruction is oncologically, aesthetically, and functionally justifiable in cases with proximity to the skin. From 2010 to 2016, 16 patients underwent skin-preserving excision of T1-2 N0 SCCNV by a lateral rhinotomy approach at a tertiary referral center. The inner nose was reconstructed using a mucoperichondrial septal flap for the inner lining and a septal pivot flap and/or auricular cartilage grafting for the framework. Nasal appearance was measured on pre- and postoperative photographs. Median follow-up was 5.4 years. Three (19%) patients received adjuvant radiotherapy. Two (12.5%) recurrences occurred locally, but not at the site of preserved skin. The Kaplan-Meier estimate of local control rate after 5 years was 83%. All patients could be salvaged, giving an ultimate control rate of 100%. Nasal tip projection decreased by 6.7% (p < 0.001), and it was retained normal or near normal in 87.5% of patients. Nasal axis changed by 1.7° (p=0.5). Nasal deviation occurred in 6.25% (1/16) of patients, and minor alar retraction in 6.25% of patients (1/16). Nasal breathing was normal or close to normal in 75% (12/16) of patients. Skin-preserving excision of SCCNV is oncologically justifiable in selected cases even in proximity to nasal skin. Early inner nasal reconstruction preserves nasal form and function to a high degree. This technique is a suitable alternative to rhinectomy and to avoid the sequelae of radiotherapy in selected cases.